2018
DOI: 10.1017/s0031182018000860
|View full text |Cite
|
Sign up to set email alerts
|

Anti-α-Gal antibodies detected by novel neoglycoproteins as a diagnostic tool for Old World cutaneous leishmaniasis caused byLeishmania major

Abstract: Outbreaks of Old World cutaneous leishmaniasis (CL) have significantly increased due to the conflicts in the Middle East, with most of the cases occurring in resource-limited areas such as refugee settlements. The standard methods of diagnosis include microscopy and parasite culture, which have several limitations. To address the growing need for a CL diagnostic that can be field applicable, we have identified five candidate neoglycoproteins (NGPs): Galα (NGP3B), Galα(1,3)Galα (NGP17B), Galα(1,3)Galβ (NGP9B), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Our previous studies showed that the sera of OWCL patients from Saudi Arabia contain elevated levels of anti-α-Gal IgG antibodies 45 that partially recognize simple α-Gal-containing saccharides, but a specific α-Gal BMK remained elusive. 46 Therefore, we shifted our focus to α-galactopyranose- and β-galactofuranose-containing saccharides of the terminal, nonreducing glycan portions of type-2 GIPLs of L. major . The synthesis of a terminal trisaccharide of type-2 GIPLs and a heptasaccharide present in LPGs of Leishmania parasites has been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that the sera of OWCL patients from Saudi Arabia contain elevated levels of anti-α-Gal IgG antibodies 45 that partially recognize simple α-Gal-containing saccharides, but a specific α-Gal BMK remained elusive. 46 Therefore, we shifted our focus to α-galactopyranose- and β-galactofuranose-containing saccharides of the terminal, nonreducing glycan portions of type-2 GIPLs of L. major . The synthesis of a terminal trisaccharide of type-2 GIPLs and a heptasaccharide present in LPGs of Leishmania parasites has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent study, we assayed several other NGPs containing other α-Gal-glycotopes linked to BSA, including α-Gal p ( NGP3b ), Gal p α1,3Gal p α ( NGP17b ), Gal p α1,3Gal p β ( NGP9b ), Gal p α1,6[Gal p α1,2]Gal p β ( NGP11b ), and Gal p α1,3Gal p β1,4Glc p β ( NGP1b ). 46 When assayed by chemiluminescent ELISA with sera from L. major- infected patients with active CL lesion ( n = 17) or cured ( n = 29) or sera from heterologous diseases, the most promising diagnostic potential (AUC ROC = 0.8) was observed with NGP3b (α-Gal p –BSA). Although this AUC value is considered acceptable for a diagnostic test, a higher accuracy (AUC = 0.9–1.0), as we observed in most ROC curves in this study, is desirable.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-Leishmania antibodies are barely detectable in CL and to some extent these can be detected in ML and DCL but with limited and variable performance [62]. New opportunities for the serological diagnosis of CL may be brought by the detection of anti-α-Gal antibodies, with promising preliminary results for Old World leishmaniasis, nevertheless this field requires further research [72].…”
Section: Unlike In Vl CL Is Not Characterized By An Elevated Productmentioning
confidence: 99%
“…α-Gal immunity has been studied in other parasites, such as Leishmania major and Plasmodium falciparum . Neoglycoproteins containing α-Gal have been described as diagnostic tools for cutaneous leishmaniasis [ 110 ] and for protection against the parasite [ 111 , 112 ]. In Plasmodium falciparum , the agent of malaria, terminal α-linked galactosyl units, recognized by immune sera, are present in carbohydrate chains of glycoproteins [ 113 , 114 ].…”
Section: Structure Of Glycans In Mucins From Mammalian Cell-derivementioning
confidence: 99%